Silver-induced self-immolative Cl–F exchange fluorination of arylsulfur chlorotetrafluorides: synthesis of arylsulfur pentafluorides. Issue 95 (17th October 2017) - Cui, Benqiang; Jia, Shichong; Tokunaga, Etsuko; Saito, Norimichi; Shibata, Norio
Abstract : Cl–F exchange fluorination of (Het)ArSF4 Cl without fluorinating reagents is disclosed. Abstract : A novel strategy for the synthesis of arylsulfur pentafluorides by silver carbonate-induced Cl–F exchange fluorination of arylsulfur chlorotetrafluorides is reported. This fluorination does not require any exogenous fluoride sources. Rather, the reaction proceeds via the self-immolation of the substrate Ar-SF4 Cl.